Memorable Shaadi - Sud, Mukesh; Sharma, Supriva; Mendonca, Valerie (London : Indian Institute of Management, Ahmedabad, 2017)
Ujwal Kalra founded Memorable Shaadi in mid-2014 as an alternate career option, when he failed to get admission into the Indian Institute of Management, Ahmedabad (IIMA). The venture was motivated by Ujwal's personal experiences and difficulties with organising his sister's wedding. The venture offered services as a liaison between clients and vendors in the Indian wedding industry. It was designed to be a marketplace where clients could discover and contact vendors offering a variety of wedding-related services. It partnered with various vendors for a discounted rate and shared about half the discount with clients. The services were provided by the vendors while their quality was assured by Memorable Shaadi, which differentiated it from other wedding planners. Over the course of two years, Memorable Shaadi had a steep learning curve. It began with the aim of onboarding a large number of vendors so as to provide a wide variety to customers. Learning from the disloyalty of some vendors and from issues of poor quality, Memorable Shaadi developed criteria to evaluate vendors and worked only with those who rated high on three parameters - quality, loyalty and competitive price. After running Memorable Shaadi for one year, when Ujwal was offered admission to IIMA, Vishu, a close friend, stepped in to lead the venture. Now that Ujwal's course is close to completion, he is faced with the dilemma of whether to accept a coveted consulting job or go back to Memorable Shaadi.
Originally Published InSud, M., Sharma, S., & Mendonca, V. (2017). Memorable Shaadi. Ahmedabad, IN: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Weddings -- India -- Planning -- Case studies; Weddings -- India -- Economic aspects -- Case studies